Who lived around Mecca during the 7th and 8th centuries - Al - Balawi, Shadia Abdel Rahman (Journal of Humanities & Social Sciences, 2017)
Mecca has received the sanctity and place in the hearts of Muslims a lot of different writings that covered various political and cultural aspects of its history through different ages, yet we note through our study that Mecca, despite its great importance, but the sources of Islamic history were keen on The history of Mecca since the time of the Prophet peace be upon him until the middle of the second century AH, on the day of Mecca was the center of political activity and scientific alike, and then began to diminish this concern, especially since the beginning of the third century AH, these sources are no longer provide us only a little Nazer focused primarily On The history of religious Mecca, such as the pilgrimage to people and so on, rarely refer to the aspects of political life, economic and civilization of this country, but this little information with the written historian Makkah Azraqi and Fakhi in the third century, provides the researcher important information about the history of Mecca during the first three centuries, Historians Azraqi in the year 250 AH and Fakhi in the year 280 AH entered the history of Mecca in the almost forgotten, and surrounded by the mystery, which lasted for five centuries, that the rule of God has a historian of its children in the eighth century AH is Taqi al-Din Fassi Fassi felt the vacuum experienced by historians Mecca m A drive on the classification of books bosses (precious decade) and (healing gram), two of the most important books that relied upon in my study of the neighboring Mecca, and given the importance of this layer (Majaoron) in Mecca society and its substantial role in which it has signed an optional on this subject to search.
Keywords: Neighbors; Mecca; Seventh and Eighth Centuries; Migration